ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU TUNJUK AJAR MELAYU KARYA TENAS EFFENDY - Sayyidah Raihaninur; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is motivated by the increasing number of cases of social phenomena that we often see today, for example students who often skip classes during classes, students who often fight, promiscuity, drugs and other actions violate the norm. The need for character education needs that undermine the morals of the nation's children is embedded in everyday life. Character education encourages students to apply the values of goodness in real actions or daily behavior that relate to God Almighty, oneself, fellow human beings, the environment, and the nation and state. Quality characters need to be formed and nurtured from an early age. Early age, especially elementary age is a critical period for the formation of one's character. In this study, researchers examined the values of character education contained in the book "Tunjuk Ajar Melayu" by Tenas Effendy. Malay teaching appointments contain various noble values that can be used as guidelines and will live, which are full of noble values of Islamic religion and culture. The purpose of the research in this paper is to describe the values of character education contained in the book Tunjuk Ajar Melayu" by Tenas Effendy according to the character of elementary students. This research is descriptive. The data of this study are data in the book " Tunjuk Ajar Melayu" which is associated with character education values. The research subjects were researchers took 6 teaching points and 2 advice from the book " Tunjuk Ajar Melayu" " as research material. After the researchers examined the values of 18 character education values, only 8 characters studied were religious, honest, hard work, independent, friendly / communication, caring for the social, caring for the environment and responsibility. Total values of relevan religious character education 16 data, honest 4 data, hard work 3 data, independent 4 data, 4 data responsibilities, social care 4 data, care for the 5 data environment and friendly / communication 3 data.Key Words : Education Character, Tunjuk Ajar Melayu